The impact of mayor leadership on education: evidence from Brazil - Barbosa, Mariana Carvalho (2015)
What are the impacts of female mayors on education? It is well known that in Brazil, like in many other countries around the globe, women are underrepresented in political posts. Understanding the impacts of this discrepancy on policy choice and redistribution across many areas of inquiry is, therefore, an important research endeavor. Extant literature shows a strong link between women and the economic development of the areas they govern, specifically that they provide public goods relevant to the needs of women constituents. However, despite the efforts to explore the impacts of gender political leaders, we still do not know what is the consequence of gender on policy outcomes. Exploring a rich dataset on Brazilian municipalities, I intend to enrich the literature on the role of female politicians on politics. I employ a regression discontinuity design using Brazilian elections and indicators on education based on the basic education development index (IDEB), education expenditures and local policies. I find that municipalities where a woman enters into power do not perform better on education and do not present more investments or policies to improve education.